2006
DOI: 10.1073/pnas.0606236103
|View full text |Cite|
|
Sign up to set email alerts
|

A molecular mechanism for osmolyte-induced protein stability

Abstract: CorrectionsNEUROSCIENCE. For the article ''A molecular neuroethological approach for identifying and characterizing a cascade of behaviorally regulated genes,''

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
583
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 624 publications
(616 citation statements)
references
References 38 publications
(38 reference statements)
28
583
2
3
Order By: Relevance
“…Several groups have begun examining preferential hydration contributions from the dependence of exclusion on the chemical character of the exposed surface (33)(34)(35). Bolen and coworkers (11,36), for example, have measured the dependence of the solubility of amino acids and amino acid derivatives on solute concentration in order to estimate the contributions from the peptide backbone and side chains. The Schellman model (37) is commonly taken as the physical basis for exclusion, combining steric exclusion or crowding and a relative solute-water binding constant for solvation interactions with the macromolecule.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have begun examining preferential hydration contributions from the dependence of exclusion on the chemical character of the exposed surface (33)(34)(35). Bolen and coworkers (11,36), for example, have measured the dependence of the solubility of amino acids and amino acid derivatives on solute concentration in order to estimate the contributions from the peptide backbone and side chains. The Schellman model (37) is commonly taken as the physical basis for exclusion, combining steric exclusion or crowding and a relative solute-water binding constant for solvation interactions with the macromolecule.…”
Section: Discussionmentioning
confidence: 99%
“…Stabilization can also arise when the free energy of transferring a peptide bond from a dilute aqueous solution to an aqueous solution containing the cosolute is unfavorable (Timasheff 1993). This preferential hydration of N is stabilizing because unfolding exposes more backbone to cosolutes (Street et al 2006). In summary, unlike hardcore repulsions, which are always stabilizing, non-specific interactions can be stabilizing or destabilizing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that osmolytes such as TMAO can enhance protein folding, ligand binding and can counteract perturbations caused by urea or inorganic ions [22][23][24] . Therefore, it is possible that TMAO affects the structure of receptors and peptide hormones such as Ang II, and may be not only a marker of increased cardiovascular risk, but also a mediator in etiology of cardiovascular diseases.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%